Unusual Mass Spectrometric Dissociation Pathway of Protonated Isoquinoline-3-Carboxamides Due to Multiple Reversible Water Adduct Formation in the Gas Phase - Beuck, Simon; Schwabe, Tobias; Grimme, Stefan; Schlörer, Nils; Kamber, Matthias; Schänzer, Wilhelm; Thevis, Mario (Journal of the American Society for Mass Spectrometry, 2009)
The study of the collision-induced dissociation behavior of various substituted isoquinoline-3-carboxamides, which are amongst a group of drug candidates for the treatment of anemic disorders (e.g., FG-2216), allowed for the formulation of the general mechanisms underlying the unusual fragmentation behavior of this class of compounds. Characterization was achieved with high-resolution/high accuracy LTQ-Orbitrap tandem mass spectrometry of the protonated precursor ions. Presented data were substantiated by the synthesis and analysis of proposed gas-phase intermediate structures and stable isotope labeled analogues, as well as by density functional theory calculations. Exemplary, CID of protonated N-[(1-chloro-4-hydroxy-7-isopropoxy-isoquinolin-3-yl)carbonyl]glycine gives rise to the isoquinoline-3-carboxy-methyleneamide product ion which nominally eliminates a fragment of 11 u. This was attributed to the loss of methyleneamine (−29 u) and a concomitant spontaneous and reversible water addition (+18 u) to the resulting acylium ion to yield the protonated isoquinoline-3-carboxylic acid. The same water addition pattern is observed after loss of propylene (−42 u). A further nominal loss of 10 u is explained by the elimination of carbon monoxide (−28 u) followed by another water adduct formation (+18 u) to yield the protonated 1-chloro-3,4,7-trihydroxy-isoquinoline. The source of the multiple gas-phase water addition remained unclear. This atypical fragmentation pattern proved to be highly characteristic for all studied and differentially substituted isoquinoline-3-carboxamides, and offers powerful analytical tools for the establishment of a LC/MS(/MS) based screening procedure for model HIF-stabilizers and their potential metabolites in clinical, forensic and sports drug testing. The loss of 11 u in ESI-MS/MS spectra of isoquinolines was elucidated. The release of methyleneamine accompanied by an ion-molecule reaction with water was proven.